PENGEMBANGAN MEDIA KOMIK PADA MATERI SUMBER ENERGI TERHADAP HASIL BELAJAR KELAS III SD NEGERI 3 RAMBUTAN - Kurnia, Kurnia; Retta, Allen Marga; Ayurachmawati, Puji (STKIP Persada Khatulistiwa Sintang, 2024)
The aim of the research is to develop comic media to determine the validity, practicality and potential effects of the comic media being developed. The type of research applied is Research and Development (R&D) with the ADDIE method which consists of Analyze, Design, Development, Implementation and Evaluation. The research results from the development of comic media on energy source materials were valid. It can be seen from the assessment results from media, material and language experts, obtaining a percentage of 87% with the criteria